Village Muslim as a Symbol of Resistance to the Transnational Islamic Movement in Yogyakarta - Ashari, Muh. Subhan; Fitriyaturrosyidah, Farida (YASIN, 2025)
This study explores the underlying factors driving the resistance of village Muslims to the transnational Islamic movement through the lens of Islamic boarding school (pesantren) development in Yogyakarta, as well as the ongoing dynamics that have led to prolonged conflict. Employing a qualitative case study approach, the research investigates how socio-religious tensions emerge and persist within local contexts. The findings identify two primary causes of resistance: the absence of a symbiotic relationship between village Muslims and transnational Islamic actors, and a lack of effective communication with the local community. These factors have sustained resistance over time, marked by cultural and political negotiations in response to symbolic differences in daily religious practices. The resulting disharmony illustrates how local identity and religious expression diverge from those promoted by transnational movements. Viewed through the lens of human needs theory, the conflict reflects a struggle to preserve deeply rooted communal ideals and identity. Ultimately, the study concludes that religious identity serves as the central force motivating village Muslims to uphold their values and resist external pressures, underscoring the complexity of religious interaction at the grassroots level.